Robust Controller Design for Networked Control Systems Based on State Estimation - Fengxia None Xu; Qunhong None Tian; Junke None Wang; Mengkun None Li (Institute of Advanced Engineering and Science, 2014)
For the networked control systems with uncertain time delay in both sensor-to-controller and controller-to-actuator channels, and data dropouts in sensor-to-controller channel, a new model of networked control systems based on state estimation is proposed using single-exponential smoothing method to predict the state variables. After adopting Lyapunov stability theory, the asymptotic stability for the system has been proved, and the Robust Controller has been designed by using linear matrix inequality. In the simulation experiment, comparing the state responses under different situations of diverse time delay and data dropouts, the results show that the method is effective.